Systemic inequality, sustainability and COVID-19 - Aladuwaka, Seela; Wejnert, Barbara; Alagan, Ram (Research in political sociology ;, 2022)
The global spread of COVID-19 has led to devastating effects on countries worldwide in terms of population health, economy, politics, and sustainable development. Systemic Inequality, Sustainability and COVID-19 provides an opportunity to engage in a critical dialog on the consequences and interactions of COVID-19 with social inequalities and environment management. The pandemic has shattered personal lives, families, businesses, countries' health systems, education, economy, and sustainable development. COVID-19's impact is most visible among disadvantaged populations as the pandemic amplified the already profound social inequalities and problems of environmental justice existing in developed and developing countries alike. Understanding that it is critical to determine the scope, magnitude, and scale of pandemic effects on the most vulnerable groups and environmental sustainability, this book addresses the impact of COVID-19 on countries' development, exploring the consequences and interactions of COVID-19 with social inequalities and sustainable development. Taking a global perspective, this edited collection is vital to understanding countries' progress and development during and after the pandemic in this extraordinary moment in human history.